Pengaruh Burnout Academic Terhadap Perlaku Konsumtif Mahasiswa - Rita Anggun Wahyuni; Agus Salim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Purchasing behavior can change when someone is under pressure or stress, especially when they are at a high level of stress or when experiencing academic burnout, this phenomenon is related to a person's stress level and their shopping behavior at a certain time. This study was conducted to determine the effect of academic burnout on student consumer behavior. Using a quantitative correlational research method. The subjects in this study were all active students in the Special Region of Yogyakarta with a sample of 150 people. The research data were analyzed using the classical assumption test and hypothesis test. the results of this study found that there was a very significant influence of academic burnout on student consumer behavior. This is indicated by a significance value of 0.010 which indicates that the higher the academic burnout, the higher the consumer behavior in students. . The weakness in this study is related to the sample that focuses only on the Special Region of Yogyakarta. so that further research is expected to use a wider sample.